2017
DOI: 10.1186/s13059-017-1226-y
|View full text |Cite
|
Sign up to set email alerts
|

The developmental regulator PKL is required to maintain correct DNA methylation patterns at RNA-directed DNA methylation loci

Abstract: BackgroundThe chromodomain helicase DNA-binding family of ATP-dependent chromatin remodeling factors play essential roles during eukaryote growth and development. They are recruited by specific transcription factors and regulate the expression of developmentally important genes. Here, we describe an unexpected role in non-coding RNA-directed DNA methylation in Arabidopsis thaliana.ResultsThrough forward genetic screens we identified PKL, a gene required for developmental regulation in plants, as a factor promo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 81 publications
(144 reference statements)
1
35
0
Order By: Relevance
“…It is also possible that mobile maternal p4-siRNAs are required for correct expression of specific transposon-associated genes, such as AGAMOUS-like transcription factors, which are upregulated in Arabidopsis seeds lacking maternal NRPD1 (Lu et al, 2012). Finally, mobile maternal p4-siRNAs might function across the genome to maintain the effective parental dosage in endosperm and their loss could unbalance parental contributions and lead to endosperm failure (Gehring, 2013;Yang et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…It is also possible that mobile maternal p4-siRNAs are required for correct expression of specific transposon-associated genes, such as AGAMOUS-like transcription factors, which are upregulated in Arabidopsis seeds lacking maternal NRPD1 (Lu et al, 2012). Finally, mobile maternal p4-siRNAs might function across the genome to maintain the effective parental dosage in endosperm and their loss could unbalance parental contributions and lead to endosperm failure (Gehring, 2013;Yang et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…However, the silencing of FWA in the vegetative tissue by DNA methylation suggests a minimal role of FWA in flowering time regulation [ 70 ]. Interestingly, PICKLE (PKL), a chromatin remodeling factor, plays a role in non-coding RNA-directed DNA methylation by maintaining the levels of CG, CHG, and CHH methylation [ 71 ]. pkl-1 mutants exhibit late flowering and reduced the hypocotyl elongation at a warm temperature [ 72 , 73 ].…”
Section: Histone Variants Histone Modification and Dna Methylatimentioning
confidence: 99%
“…More than 600 genes were differentially expressed between the wild-type and pkl mutant plants after cold treatment, including the downregulation of CBF3 and multiple CBF target genes, such as RD29A , COR15A , and COR15B . Since PKL is known to be involved in the RdDM [ 32 ] and H3K27me3 deposition [ 33 ] pathways, both H3K27me3 and DNA methylation could serve as memory marks for cold-induced freeze tolerance.…”
Section: Epigenetic Responses To Stressful Factorsmentioning
confidence: 99%
“…In evolution, they elaborate specific adaptive mechanisms to overcome various kinds of environmental stress and retain the stress response information for some time after the stress encounters are over. It was shown that stress factors induce alterations in the epigenetic status of stress-response genes that could still be present for some time after recovery or even in the progeny [ 32 , 42 , 45 , 47 , 83 ]. This kind of information used by plants to respond faster or stronger at repeated exposure to the same stress was named stress priming or stress memory [ 45 , 84 ].…”
Section: Short-term Epigenetic Memory (Priming) Of Stressmentioning
confidence: 99%